Modeling Adeno-Associated Virus (AAV) Gene Therapy: When Systems Biology met Systems Pharmacology. Issue 23 (2022) - Pichardo-Almarza, Cesar; Kimko, Holly
Abstract: Gene therapies based on adeno-associated virus (AAV) have been identified as promising treatments for a variety of diseases where conventional treatments are unavailable or have not been efficient. Given the complexity in the biological mechanisms related to gene therapy and the small number of subjects in potential clinical trials, conventional pharmacokinetic (PK) modelling approaches used alone or in combination with classical statistical techniques for the analysis of inter-individual variability explained by covariates cannot be used to the estimate the right dose for various subjects. This work shows how a classical systems biology model originally developed to understand the dynamics of adeno-associated viruses was extended to create a quantitative systems pharmacology (QSP) tool that can be used to decide gene therapy doses for different diseases. An example of the method applied for AAV gene therapy of hemophilia B patients is shown.